Web-Based Employee Recruitment Information System: A Design Study - Abdul Khair Junaidi (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2025)
The advancement of information technology has encouraged companies to undergo digital transformation across various operational aspects, including employee recruitment. Manual recruitment processes often create challenges such as administrative delays, data duplication, and limited access to information. This literature review aims to examine the concepts, benefits, and previous research findings related to the design of web-based employee recruitment information systems. The study adopts a qualitative approach through a review of various academic sources, including journals, books, and research reports related to information systems and human resource management. The findings indicate that web-based recruitment systems improve time efficiency, data accuracy, and transparency in the selection process. Furthermore, such systems simplify the application process for job seekers and support HR departments in conducting data-driven analyses and decision-making. Previous studies have also highlighted that the adoption of web-based systems can enhance recruitment quality by 40–60% compared to manual methods. This study emphasizes the importance of integrating information technology into human resource management as a strategic step toward organizational digitalization.